2014 6th IEEE Power India International Conference (PIICON) 2014
DOI: 10.1109/34084poweri.2014.7117730
|View full text |Cite
|
Sign up to set email alerts
|

Small signal stability analysis of grid connected distributed PV and wind energy system

Abstract: Reliability and sustainability are the real problems of today's complex power systems. These challenges are met by increasing the renewable generation. With increase in penetration of renewable resources, mostly solar and wind generation, power systems are expected to experience changes in operational and dynamic characteristic. This work investigates the impact of penetration of distributed solar photovoltaic generation and DFIG based wind generation on small signal stability of power systems. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The main focus of this paper was to improve the stability for the lower frequency NS-A mode. Krishan et al (2014) investigated the penetration of distributed solar PV-and DFIG-based wind generation in power systems. Here, different modes such as local mode, interarea mode and critical mode of the system were allocated by using the grid-connected distributed PV generation.…”
Section: Related Workmentioning
confidence: 99%
“…The main focus of this paper was to improve the stability for the lower frequency NS-A mode. Krishan et al (2014) investigated the penetration of distributed solar PV-and DFIG-based wind generation in power systems. Here, different modes such as local mode, interarea mode and critical mode of the system were allocated by using the grid-connected distributed PV generation.…”
Section: Related Workmentioning
confidence: 99%
“…It was found that the stability margin of the system is enhanced considerably [5]. Based on [6], penetration of DFIG wind turbines of almost 2MW in a wind farm shows an improvement in the of the power system stability when aggregated under certain conditions on a small grid.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [5], small signal stability analysis for grid connected PV and wind energy was investigated via PSAT Toolbox of MATLAB under 3 cases which is the base case, load disturbance and effect of configuration changed. Results indicate that the stability margin improved.…”
Section: Introductionmentioning
confidence: 99%